Antidepressant-like effects of trophic factor receptor signaling - Sathyanesan, Monica; Newton, Samuel S. (Frontiers in Molecular Neuroscience, 2022)
A significant body of research has demonstrated that antidepressants regulate neurotrophic factors and that neurotrophins themselves are capable of independently producing antidepressant-like effects. While brain derived neurotrophic factor (BDNF) remains the best studied molecule in this context, there are several structurally diverse trophic factors that have shown comparable behavioral effects, including basic fibroblast growth factor (FGF-2), insulin-like growth factor 1 (IGF-1) and vascular endothelial growth factor (VEGF). In this review we discuss the structural and biochemical signaling aspects of these neurotrophic factors with antidepressant activity. We also include a discussion on a cytokine molecule erythropoietin (EPO), widely known and prescribed as a hormone to treat anemia but has recently been shown to function as a neurotrophic factor in the central nervous system (CNS).